Democratic dialogue and the constitution - Young, Alison L. (Oxford : Oxford University Press, 2017)
Focusing on the protection of rights in the UK, this book establishes a framework for interactions to better protect rights, facilitate deliberation, engage citizens and provide for checks and balances. It further evaluates how well these values are achieved in the UK constitution now, and in light of a British Bill of Rights and Brexit.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 16, 2017).
Keywords: Constitutional law -- Great Britain; Human rights -- Great Britain; Law; Laws of specific jurisdictions & specific areas of law